Knowledge, Attitude and Practice of Prophylaxis for Malaria Treatment Among Pregnant Women Attending Clinic in Edo State, Nigeria: Implications for Counselling - Osumah, Obaze Agbonluae; Edeme-Okonigene, Dorcas (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2025)
Malaria infections are generally asymptomatic, and the current control strategy is based on the prevention of infections. The study examined the knowledge, attitude and practice of prophylaxis of malaria treatment among pregnant women attending clinic at primary health centres, Ujoelen, Edo State, Nigeria. The study adopted the descriptive survey research design. The sample size of 60 pregnant women attending clinic at primary health centres, Ujoelen, Edo State, Nigeria was used for this study. Questionnaire was the instrument used to collect data. Results were analysed using simple descriptive data analysis of frequencies and percentages. Findings from the study revealed that the respondents had a high level of knowledge of prophylaxis of malaria treatment, negative or poor attitude towards prophylaxis of malaria treatment and poor practice prophylaxis of malaria treatment. The study concluded that respondents had a high level of knowledge of prophylaxis of malaria treatment, negative or poor attitude towards prophylaxis of malaria treatment and poor practice prophylaxis of malaria treatment. It is therefore recommended that concerted effort be put in place by the nurses, more especially public health nurses to address the barriers to the practice of prophylaxis of malaria treatment. This could be done through mass health education to market women at regular interval. Pregnant women should be encouraged to seek the advice of public health officers regarding prevention of malaria.